DIALOG TERSTRUKTUR UNTUK PEMUDA: REKOMENDASI UNTUK REALISASI KOMUNITAS ASEAN 2015 DI INDONESIA - Felix Sharief (Jurnal Universitas Paramadina, 2013)
AbstractOne of the mandates set out in ASEAN Charter, ASEAN Socio-CulturalCommmunity Blueprint and the vision of Indonesia’s Chairmanship in 2011is to have a more people-oriented of ASEAN. The youth may the society andact as an agents of change in this nation have a significant role in achievingthis goal. European Union as ASEAN’s aspiration for regional integrationhas been using a mechanism of structured dialogue to bolstering youngpeople engagement in whole sectors. Stuctured dialogue aims to discusschosen themes with young people, in order to obtain results which are usefulfor policy-making. This paper will review the possibility of such mechanismto be implemented in Indonesia.